Mediated narration in the digital age : storying the media world - Gloviczki, Peter Joseph (Lincoln : University of Nebraska Press, 2021)
Peter Joseph Gloviczki provides a history of new media technology that examines mediated narration from 1991 through 2018.
Storying as an Active Process -- 1. Storying the Media World -- 2. Storying Sandy Hook -- 3. Storying FDR -- 4. Storying "Seven Days of Heroin" -- 5. Storying the Future
Includes bibliographical references and index.
Online resource; title from PDF title page (viewed on September 2, 2021).
eBooks on EBSCOhost
Keywords: Narration (Rhetoric) -- Case studies; Online journalism -- United States -- Case studies; Digital storytelling -- United States -- Case studies; Storytelling in mass media -- Case studies; Narration -- Études de cas; Journalisme en ligne -- États-Unis -- Études de cas; Récits numériques -- États-Unis -- Études de cas; Art de conter dans les médias -- Études de cas; LANGUAGE ARTS & DISCIPLINES / Journalism; SOCIAL SCIENCE / Media Studies; Storytelling in mass media; Online journalism; Narration (Rhetoric); Digital storytelling; United States; Case studies